Savoir intime dans l’apprentissage de l’écriture - Sandra Cadiou (Recherches en Éducation)
It is within the framework of the Clinical Didactics (Carnus, Terrisse, 2009, 2013) based on the hypothesis of the Freudian unconscious, that we investigate the learning of writing fiction in vocational high schools. How does this involve psychic work? Didactic conversion in the student (Cadiou, 2016, 2018) is a disciplinary knowledge rooted in psychic elements. This writing skill appears in the student text, but why does he choose one textual form over another? The notion of intimate knowledge could explain this. We observed four students during a sequence « write a short story with a surprising ending » in French class. Our corpus (semi-directed interviews, courses, written texts) is treated with a 3-step methodology (the already-there, the test and the post-coup) which allows the construction of cases. According to our results, the psychic work induced by the learning of writing would create intimate knowledge of the subject's position about the enjoyment and then could be an important parameter.